IMPLEMENTATION OF PROBLEM-BASED LEARNING AND GROUP INVESTIGATION (PBL GO-IN) TO IMPROVE VOCATIONAL STUDENTS’ COMPETENCE - Hendy Purnomo; Budi Santosa; Fatwa Tentama (Universitas Ahmad Dahlan, 2019)
The purpose of this study was to determine the effectiveness of a combination of problem-based learning and group investigation (PBL Go-In) methods on the competence of the Motorcycle Engineering and Business Program students. This study is an experimental implementation method using quasi-experimental design with a non-equivalent control group design. The results of the study obtained the application of the PBL Go-In model consisting of 7 stages, namely, presentation of problem situations, investigation and exploration, formulation of tasks, learning activities, analysis of progress, presentation, and assessment. The results of the analysis suggest that there are differences in the level of competency of students before and after the PBL Go-In method is implemented. The percentage of students passing minimum grade of 75 before treatment was 8.7%, and after treatment became 82.6%. Thus, it can be said that PBL Go-In learning model is potential to improve the students competence.